Oecanthus buxixu sp. nov. (Orthoptera: Grylloidea: Oecanthidae): A new species of tree cricket from Brazilian Amazon rainforest - Acosta, Riuler Corrêa; Mendes, Diego Matheus De Mello; Ramalho, Emiliano Esterci; Zefa, Edison (Zootaxa, 2024)
The Tree Crickets of the genus Oecanthus Serville, 1831 are distributed across tropical and temperate regions, where they can be found in all strata of vegetation. In this work, we describe a new species of tree cricket from the Brazilian Amazon rainforest, where only one species was known until the date of this publication. This new species differs from the other 79 species in this genus by the absence of marks on the scape and pedicel of the antennae, as well as by its calling song composed of 3 to 5 chirps/s, 6 to 20 pulses per chirp, and peak frequency 3 to 3.3 kHz, at 26ºC. Photos in vivo of the individuals, as well as images of the metanotal glands and phallic sclerites, are provided.